2016
DOI: 10.1523/jneurosci.0897-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of the Functional Alterations of Motor Cortical Circuits in Arginase Deficiency by Neonatal Gene Therapy

Abstract: Arginase 1 deficiency is a urea cycle disorder associated with hyperargininemia, spastic diplegia, loss of ambulation, intellectual disability, and seizures. To gain insight on how loss of arginase expression affects the excitability and synaptic connectivity of the cortical neurons in the developing brain, we used anatomical, ultrastructural, and electrophysiological techniques to determine how single-copy and double-copy arginase deletion affects cortical circuits in mice. We find that the loss of arginase 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…P2 AAV hepatic gene therapy rescued the defects associated with myelinated axons in the regions examined and strongly implicates the functional recovery of oligodendrocytes after gene therapy. Secondly, by extending our previous studies (18), we further demonstrated that P2 AAV hepatic gene therapy can rescue the defects of excitatory synaptic density and perforated synapses in layer V of the Arg1-KO motor cortex up to 4 months of age, strongly indicating that early postnatal treatment can drastically change the synaptic organization in layer V and ultimately lead to recovery of function in the corticospinal pathway. Dendritic arborization and soma size are altered in Arg1 deficiency.…”
Section: Figure 2 Microarray Expression Studies Of the Brain In Argisupporting
confidence: 74%
See 3 more Smart Citations
“…P2 AAV hepatic gene therapy rescued the defects associated with myelinated axons in the regions examined and strongly implicates the functional recovery of oligodendrocytes after gene therapy. Secondly, by extending our previous studies (18), we further demonstrated that P2 AAV hepatic gene therapy can rescue the defects of excitatory synaptic density and perforated synapses in layer V of the Arg1-KO motor cortex up to 4 months of age, strongly indicating that early postnatal treatment can drastically change the synaptic organization in layer V and ultimately lead to recovery of function in the corticospinal pathway. Dendritic arborization and soma size are altered in Arg1 deficiency.…”
Section: Figure 2 Microarray Expression Studies Of the Brain In Argisupporting
confidence: 74%
“…Hypothesis I: Deficiency of arginase 1 results in CNS dysmyelination. In our previous study (18), we demonstrated that, in motor cortex layer V of Arg1-KO mice at P15, a significant decrease in both the density of asymmetrical synapses and AMPA receptor-enriched (AMPAR-enriched) perforated synapses (19)(20)(21) corresponded with a malfunction in glutamatergic excitatory synaptic transmission. We also found in that study that intrinsic excitability is altered in proportion to the copy number loss of arginase and that the circuit connectivity is altered in KO neurons, as shown in the electrophysiological studies by decreased frequencies of miniature excitatory postsynaptic currents (mEPSCs) and the decrease in amplitude of miniature inhibitory postsynaptic currents (mIPSCs).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The reduction of the neurological symptoms and the decrease of the levels of arginine and ammonia are essential [49,50].…”
Section: Conflict Of Interestmentioning
confidence: 99%